The value of A for which [5+(-3)]+(-4)=A+[(-3)+(-4)] is true is
Grimasingh88:
please give answer
Answers
Answered by
2
Answer:
5
Step-by-step explanation:
[5+(-3)]+(-4)=A+[(-3)+(-4)]
therefore
[5-3)]+(-4)=A+[(-3)+(-4)]
therefore
[2]+(-4)=A+[(-3)+(-4)]
then
2-4=A+[(-3)+(-4)]
then
-2=A+[(-3)+(-4)]
then
-2=A+[(-3)-4)]
then
-2=A+[-7]
then
-2-[-7]=A
therefore
A=-2+7=5
Answered by
2
Answer:
5
Step-by-step explanation:
first from LHS
5-3=2 then 2-4=-2
from rhs
-3-4=-7 then -2-(-7) =-2+7=5
then a =5
Similar questions